2013
DOI: 10.1021/ie400507c
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Functionalized Membranes for Polychlorinated Biphenyl Degradation

Abstract: Membranes have been widely used in water remediation (e.g. desalination and heavy metal removal) because of the ability to control membrane pore size and surface charge. The incorporation of nanomaterials into the membranes provides added benefits through increased reactivity with different functionality. In this study, we report the dechlorination of 2-chlorobiphenyl in the aqueous phase by a reactive membrane system. Fe/Pd bimetallic nanoparticles (NPs) were synthesized (in-situ) within polyacrylic acid (PAA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 55 publications
(121 reference statements)
1
39
0
Order By: Relevance
“…In order to test the possible effect of ZVI on the dechlorination process, Fe loaded functionalized membranes were also studied. As demonstrated before, biphenyl is the main product of PCB degradation when using the Fe/Pd reductive pathway [33, 51]. However, for this coplanar PCB congener (i.e., PCB 126), the biphenyl yield was much lower than the theoretically attainable value.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…In order to test the possible effect of ZVI on the dechlorination process, Fe loaded functionalized membranes were also studied. As demonstrated before, biphenyl is the main product of PCB degradation when using the Fe/Pd reductive pathway [33, 51]. However, for this coplanar PCB congener (i.e., PCB 126), the biphenyl yield was much lower than the theoretically attainable value.…”
Section: Resultsmentioning
confidence: 96%
“…The first two steps were achieved by following methods developed in our lab [33]. Functionalized PAA-PVDF membranes were soaked overnight in 500 ml NaCl solution (68.4 mM) for Na + exchange, in order to increase the ability of further Fe 2+ exchange.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We recently reported the development of full-scale polyacrylic acid (PAA) functionalized polyvinylidene fluoride (PVDF) membrane with iron/iron oxide nanoparticles for combined reductive and oxidative degradation of polychlorinated biphenyls (PCBs) in groundwater [2324]. The same redox chemistry and membrane approach can be used for selenium removal from coal-fired power plant scrubber water, as iron has been reported to reduce selenate (VI) and selenite (IV) to elemental selenium (Se 0 ) and selenide (-II) [2527].…”
Section: Introductionmentioning
confidence: 99%
“…The incorporation of nanomaterials into the membranes provides added benefits through increased reactivity with different functionality. Gui et al [57] reported the dechlorination of 2-chlorobiphenyl (2-CBP) in the aqueous phase by a reactive membrane system. Fe/Pd bimetallic nanoparticles were synthesized (in situ) within poly(acrylic acid) (PAA) functionalized polyvinylidene fluoride (PVDF) membranes for degradation of polychlorinated biphenyls (PCBs).…”
Section: Carbon-halogen Bond Cleavage Of Hocs In Water Catalyzed By Pmentioning
confidence: 99%